Percutaneous biopsy of the renal mass: FNA or core needle biopsy?. Issue 6 (23rd March 2017) - Yang, Chi‐Shun; Choi, Euna; Idrees, Muhammad T.; Chen, Shaoxiong; Wu, Howard H.
Abstract : BACKGROUND: In recent years, there have been increasing indications for percutaneous renal biopsy. Fine‐needle aspiration (FNA), with or without core needle biopsy (CB), has been used increasingly in the management of renal tumors at the study institution. METHODS: A computerized search of laboratory records was conducted to retrieve FNA cases of renal masses as well as the correlating CB and/or nephrectomy specimens. The cases spanned a period of 10 years (2006‐2015). The diagnoses were classified into 5 categories: malignant, suspicious for malignancy, neoplastic, atypical, and negative/nondiagnostic. Based on the results of the nephrectomy specimens, the diagnostic rate, sensitivity, and diagnostic accuracy were calculated among 3 groups of specimens: FNA only, CB only, and combined FNA and CB. RESULTS: A total of 247 cases of FNA with 123 correlating CB and 101 follow‐up nephrectomy specimens were identified. The diagnostic rate, sensitivity, and diagnostic accuracy were 72%, 78%, and 96%, respectively, for FNA; 87%, 92%, and 94%, respectively, for CB; and 92%, 92%, and 94%, respectively, for the combined FNA and CB group. Renal cell carcinoma and its variants were the most common histologic diagnoses (112 of 174 cases; 64%). Significant diagnostic discrepancy was noted in one case: a malignant melanoma that was misdiagnosed as renal cell carcinoma in both the preoperative FNA specimen and in the CB specimen. CONCLUSIONS: In the current study, both FNA and CB demonstrated excellent diagnostic accuracy (96% and 94%, respectively). The combination of FNA and CB was found to significantly improve the diagnostic rate when compared with either FNA alone (92% vs 72%; P <.05) or CB alone (92% vs 87%). Cancer Cytopathol 2017;125:407–15 . © 2017 American Cancer Society . Abstract : Both fine‐needle aspiration (FNA) and core needle biopsy (CB) demonstrate excellent diagnostic accuracy when diagnosing renal neoplasia. There is a synergistic diagnostic advantage to combining FNA and CB techniques that appears to significantly improve the diagnostic rate when compared with FNA alone (92% vs 72%; P <.05), and also appears to be better than the use of CB alone (92% vs 87%).